The Life of Stonewall Jackson. - Cooke, John Esten, 1830-1886 (Online access with subscription: Proquest Ebook Central., 2000)
The Life of Stonewall Jackson was written while John Esten Cooke was encamped with General Andrew Jackson and his troops during the Civil War. Based on his personal observations of the General, who was often compared to Napoleon, Cooke combines them with information taken from official papers, contemporary narratives and personal acquaintances.